Pediatric B cell repertoires are enriched for naive clonal phenotypes and are shaped by distinct selection dynamics - Hsiao, Thomas; Shtewe, Areen; Hershberg, Uri (Frontiers in Immunology, 2025)
B cell development in early life sets the stage for how the adaptive immune system will function. Although little is known about B cell biology in children, especially from tissue-residing B cells, it has been previously reported that children generally possess more naive B cell repertoires with less somatic hypermutation and fewer expanded clones compared to adults. In this paper, we move beyond these findings by studying how clonal selection differs between children and adults from both blood and tissue-residing B cells. By integrating deep sequencing data of immunoglobulin heavy chains from genomic DNA from extracted tissues and blood of 15 children and 9 adults across multiple datasets, we demonstrate that B cell repertoires in children are not only less mutated, but also undergo reduced negative selection pressures. Mutated clones in children are less likely to possess a trunk compared to adults, but the relative proportion of mutated clones with trunks increases with age in children. This pattern is not observed in adults, where the fraction of mutated clones that possess a trunk has reached a steady state. Furthermore, clones in children are more likely to contain unmutated germline sequences, exhibit a greater number of viable internal nodes in their lineages, and experience less negative selection in the framework regions of their receptors. Overall, our findings show that B cell development is not merely the accumulation of mutations with age, but rather reflects a shift from flexible, broadly permissive repertoires in childhood to refined, stringently selected repertoires in adulthood. This difference in the structure of pediatric repertoires could underlie their enhanced ability to respond to novel antigens. Together, these findings provide new insights into how selection pressures shape immunity across the human lifespan.